Assessment of Linguistic Profile of Oral-Language-Proficient Hearing-Impaired Children Using Clinical Evaluation of Language Fundamentals: Fifth Edition (CELF5) - Montserrat Durán-Bouza; Lorena Pernas; Juan-Carlos Brenlla-Blanco (Children)
Background/Objectives: Specific tests for the assessment of language development and language skills in deaf children are scarce. For this reason, parent inventories and/or standardized tests that are reliable and valid in the hearing population are used. The main aim of this study was to assess the usefulness of the Clinical Evaluation of Language Fundamentals 5 (CELF5) in determining the language skills of hearing-impaired children in a comprehensive way in comparison to their hearing peers. Methods: The sample consisted of 70 deaf and 73 hearing children aged 5–11 years. Although the results show statistically significant differences in language skills between deaf and hearing children, deaf children scored around average on 8 of the 12 subtests of the CELF5. Results: Children using total communication modality had the highest scores, followed by those using oral language and sign language. The CELF5 subtests showed high internal consistency in the deaf group. A percentile scale was also developed for this population group. Conclusions: The CELF5 showed to be a reliable test for the assessment of receptive and expressive language in children with deafness who are competent in oral language. However, further research is needed to develop language assessment tests adapted to the deaf population that are sensitive to different communication modalities.